Adulticidal activity against Stegomyia aegypti (Diptera: Culicidae) of three Piper spp. - Choochote, Wej; Chaithong, Udom; Kamsuk, Kittichai; Rattanachanpichai, Eumporn; Jitpakdi, Atchariya; Tippawangkosol, Pongsri; Chaiyasit, Dana; Champakaew, Daruna; Tuetun, Benjawan; Pitasawat, Benjawan (Revista do Instituto de Medicina Tropical de São Paulo, 2006)
Three Piper species, Piper longum, P. ribesoides and P. sarmentosum, were selected for investigation of adulticidal potential against Stegomyia aegypti, a main vector of dengue and dengue haemorrhagic fever. Successive extraction by maceration with 95% ethanol showed percentage yields of ethanolic extracts, which derived from P. longum, P. ribesoides and P. sarmentosum, of 8.89, 3.21 and 5.30% (w/w), respectively. All Piper extracts illustrated an impressive adulticidal activity when tested against female mosquitoes by topical application. The susceptibility of St. aegypti females to ethanol-extracted Piper was dose dependent and varied among the plant species. The highest adulticidal effect was established from P. sarmentosum, followed by P. ribesoides and P. longum, with LD50 values of 0.14, 0.15 and 0.26 µg/female, respectively. The potential of these Piper species, as possible mosquitocides, established convincing activity for further researches to develop natural substances for combat against adult mosquitoes.